Charting the survival, health and development of extremely preterm infants: EPICure and beyond. Issue 11 (November 2016) - Johnson, Samantha; Marlow, Neil
Abstract: Major technological advances and improvements in neonatal medicine in the 1970s and 1980s resulted in significant reductions in mortality rates for babies born at extremely low gestations. In 1992, the gestational age for defining stillbirth in the UK was reduced from 28 weeks to 24 weeks reflecting the marked increase in survival for extremely preterm births. However, as the 'limits of viability' were pushed back ever further, there was increasing recognition of the high risk for residual disability amongst extremely preterm survivors. By the mid-1990s, clinicians were aware that the landscape had changed considerably for extremely preterm infants, but wide variation in survival rates between single centres and a lack of standardized developmental follow-up meant that it was difficult to gauge the impact of extremely preterm birth on a national level and to counsel parents as to the likely outcomes for their child. So in 1995, a team of neonatologists in the UK undertook the challenge of carrying out the first national epidemiological study of survival and outcomes following extremely preterm birth, and from that the EPICure Studies were born. Over the last 20 years these and other national cohort studies have helped shape neonatal care and advance our understanding of the life course consequences of extreme prematurity. Here we provide an overview of the key findings from the EPICure Studies and discuss the future challenges faced by clinicians and academics in tackling the causes, consequences and care of extremely preterm births.